An Essential Requirement for Fgf10 in Pinna Extension Sheds Light on Auricle Defects in LADD Syndrome - Zhang, Yang; Fons, Juan M.; Hajihosseini, Mohammad K.; Zhang, Tianyu; Tucker, Abigail S. (Frontiers in Cell and Developmental Biology, 2020)
The pinna (or auricle) is part of the external ear, acting to capture and funnel sound towards the middle ear. The pinna is defective in a number of craniofacial syndromes, including Lacrimo-auriculo-dento-digital (LADD) syndrome, which is caused by mutations in FGF10 or its receptor FGFR2b. Here we study pinna defects in the Fgf10 knockout mouse. We show that Fgf10 is expressed in both the muscles and forming cartilage of the developing external ear, with loss of signalling leading to a failure in the normal extension of the pinna over the ear canal. Conditional knockout of Fgf10 in the neural crest fails to recapitulate this phenotype, suggesting that the defect is due to loss of Fgf10 from the muscles, or that this source of Fgf10 can compensate for loss in the forming cartilage. The defect in the Fgf10 null mouse is driven by a reduction in proliferation, rather than an increase in cell death, which can be phenocopied by inhibiting cell proliferation in explant culture. Overall, we highlight the mechanisms that could lead to the phenotype observed in LADD syndrome patients and potentially explain the formation of similar low-set and cup shaped ears observed in other syndromes.